Pilot Study Examining Feasibility and Comparing the Effectiveness of Decision Aids for Hip and Knee Osteoarthritis: A Randomized Trial. Issue 1 (February 2019) - Mangla, Mahima; Bedair, Hany; Dwyer, Maureen; Freiberg, Andrew; Sepucha, Karen
Background. There are many patient decision aids (DAs) available, yet there is limited evidence on comparative effectiveness of different tools.Objective. To examine feasibility of a study protocol and gather preliminary data on comparative effectiveness.Methods. Adult patients seeing a surgeon to discuss treatment for hip or knee osteoarthritis were randomized to hip and knee DAs from two vendors. Pre-visit survey included Hip/Knee Decision Quality Instrument, DA usage, health literacy, and quality of life (EQ-5D). Surgical status was ascertained 6 months post-visit. We examined response rates, eligibility, and compared the two DAs on amount of use, knowledge scores, and receipt of preferred treatment.Results. Overall response rate was 58/74 (78%) and did not differ by study arm. More patients in DA-A group reported reviewing all the DAs (64.5% DA-A v. 24.0% DA-B, P = 0.003). Knowledge scores were similar across arms (55.2% DA-A v. 48.8% DA-B, P = 0.4). For DA-B, knowledge scores were higher for those who reviewed all the DAs compared with those who did not (80% knowledge v. 39% knowledge, respectively, P = 0.004), while scores for DA-A did not vary by usage (62% knowledge v. 53% knowledge, respectively, P = 0.3). A similar percentage of each group received their preferred treatment (77% v. 73%, P = 0.8). Patients who were unsure about preferred treatment at baseline were more likely to have surgery in the DA-A arm compared with the DA-B arm (55% v. 20%, P = 0.1).Limitations. Small sample; patients were only surveyed pre-visit.Conclusion. Despite having different content and formats, the two DAs had similar overall effectiveness. Patients were more likely to review all of DA-A; however, patients who reviewed all of DA-B had the highest knowledge scores.